Konsep Diri Mahasiswa Dalam Perkuliahan Micro Teaching Prodi Pendidikan Sosiologi FIS UNP - Junaidi Junaidi; Neviyarni Neviyarni (Naradidik: Journal of Education and Pedagogy, 2022)
Ideally a student teacher candidate has a good self-concept in order to complete teacher lectures properly. However, several studies reveal the low self-concept of students. This study aims to determine the condition of the self-concept of students of the Sociology Education Study Program, FIS UNP. The research methodology uses a quantitative approach. Data collection using a questionnaire. The collected data were analyzed by statistical percentage techniques. The results of the study revealed that students of the Sociology Education Study Program FIS UNP who took Micro Teaching lectures had good self-concepts. In general, their self-concept is in the high category. They think that they are a complete figure from the physical side. They are confident in their ability to manage emotions. They are also able to follow and complete lecture assignments and are proud of their achievements, including in Micro Teaching lectures. Students feel valued and able to respect their friends and feel comfortable attending classes and in the learning environment.